2005
DOI: 10.1152/ajpgi.00389.2003
|View full text |Cite
|
Sign up to set email alerts
|

Water and enzyme secretion are tightly coupled in pancreatic secretion stimulated by food or CCK-58 but not by CCK-8

Abstract: Pancreatic secretion of protein, water, chloride, and bicarbonate under basal conditions and in response to intravenous and intraduodenal stimuli were studied in awake rats fully recovered from surgery. During the basal phase of pancreatic secretion, protein output and water output were weakly correlated or uncorrelated, consistent with separate regulation and distinct cellular origin of enzyme (acinar cells) and water (duct cells), referred to as the two-component paradigm of pancreatic secretion. When pancre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 65 publications
1
27
1
Order By: Relevance
“…In contrast, in vivo studies showed differential effects of the two molecular forms on pancreatic physiology and pathology. CCK-58, but not CCK-8, strongly stimulates pancreatic fluid secretion in rats (46,62), and CCK-8, but not CCK-58, induces pancreatitis Gates were closed at 90 min before the onset of the dark phase. Directly before lights off, animals were injected with CCK-8 or CCK-58 (0.6, 1.8, and 5.2 nmol/kg ip) or vehicle (saline containing 0.1% BSA) and placed back in their home cage.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast, in vivo studies showed differential effects of the two molecular forms on pancreatic physiology and pathology. CCK-58, but not CCK-8, strongly stimulates pancreatic fluid secretion in rats (46,62), and CCK-8, but not CCK-58, induces pancreatitis Gates were closed at 90 min before the onset of the dark phase. Directly before lights off, animals were injected with CCK-8 or CCK-58 (0.6, 1.8, and 5.2 nmol/kg ip) or vehicle (saline containing 0.1% BSA) and placed back in their home cage.…”
Section: Discussionmentioning
confidence: 97%
“…Ϫ1 over a 3-h period strongly stimulated pancreatic fluid secretion in a dose-dependent fashion in an in vivo rat model (46,62). CCK-58 induces a more sustained pancreatic protein secretion than CCK-8, as shown by the return to basal values at the end of the 3-h infusion period with CCK-8, whereas protein output remained significantly elevated compared with basal in CCK-58-treated rats (46,62).…”
Section: ·Hmentioning
confidence: 93%
See 1 more Smart Citation
“…The calcium signals are tightly linked to the physiological release of inactive zymogens from the apex of the acinar cell [13] into the pancreatic duct and duodenum, where the zymogens are activated. The vast majority of studies have been carried out using cholecystokinin-8, widely thought to be the physiological secretory hormone; however, recent evidence calls this view into question, suggesting that other forms of this peptide, such as cholecystokinin-58, may in fact be more relevant [14,15] . For example, cholecystokinin-58 is the only detectable form of cholecystokinin in the rat [14] , where water and enzyme secretion are tightly coupled in pancreatic secretion stimulated by cholecystokinin-58 but not cholecystokinin-8 [15] .…”
Section: Calcium and Stimulus-secretion Couplingmentioning
confidence: 99%
“…The vast majority of studies have been carried out using cholecystokinin-8, widely thought to be the physiological secretory hormone; however, recent evidence calls this view into question, suggesting that other forms of this peptide, such as cholecystokinin-58, may in fact be more relevant [14,15] . For example, cholecystokinin-58 is the only detectable form of cholecystokinin in the rat [14] , where water and enzyme secretion are tightly coupled in pancreatic secretion stimulated by cholecystokinin-58 but not cholecystokinin-8 [15] . To resolve controversy arising from these recent in vivo observations, comparative studies of the actions of cholecystokinin-58 and cholecystokinin-8 on isolated pancreatic cells are required.…”
Section: Calcium and Stimulus-secretion Couplingmentioning
confidence: 99%